#### Answer

$-3z\sqrt[5] {z^4}$

#### Work Step by Step

$\sqrt[5] {-243z^9}=\sqrt[5] {-243}\sqrt[5] {z^5}\sqrt[5] {z^4}=-3z\sqrt[5] {z^4}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-3z\sqrt[5] {z^4}$

$\sqrt[5] {-243z^9}=\sqrt[5] {-243}\sqrt[5] {z^5}\sqrt[5] {z^4}=-3z\sqrt[5] {z^4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.